2021
DOI: 10.3390/molecules26082310
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking the Fluxional Processes of Organometallic Piano-Stool Complexes

Abstract: The correlation consistent Composite Approach for transition metals (ccCA-TM) and density functional theory (DFT) computations have been applied to investigate the fluxional mechanisms of cyclooctatetraene tricarbonyl chromium ((COT)Cr(CO)3) and 1,3,5,7-tetramethylcyclooctatetraene tricarbonyl chromium, molybdenum, and tungsten ((TMCOT)M(CO)3 (M = Cr, Mo, and W)) complexes. The geometries of (COT)Cr(CO)3 were fully characterized with the PBEPBE, PBE0, B3LYP, and B97-1 functionals with various basis set/ECP com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…The electron density of the bond critical point [ρ (BCP) ] based on Bader’s theory of atoms-in-molecules (AIM) [ 12 , 30 , 31 ] was calculated with the Multiwfn package (version 3.8) [ 32 , 33 ], and were visualized with the VMD package (version 1.9.3) [ 34 , 35 ]. Notably, the reliability of quantum mechanics (QM) computation instead of molecular dynamics (MD) simulation in the study of the fluxional processes of organometallics has been established [ 5 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…The electron density of the bond critical point [ρ (BCP) ] based on Bader’s theory of atoms-in-molecules (AIM) [ 12 , 30 , 31 ] was calculated with the Multiwfn package (version 3.8) [ 32 , 33 ], and were visualized with the VMD package (version 1.9.3) [ 34 , 35 ]. Notably, the reliability of quantum mechanics (QM) computation instead of molecular dynamics (MD) simulation in the study of the fluxional processes of organometallics has been established [ 5 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…An abundance of benchmark studies demonstrated that Minnesota density functionals performed well in large transition metal complex systems. 197,201,203,[208][209][210] In particular, M06 has attracted the most attention to multireference rearrangements or reactions involving the formation or breaking of organic and transition metal bonds. 203,211 In addition, B3LYP-D3 considering dispersive interactions achieves a good balance between computational accuracy and efficiency and is widely employed in transition metal-involved coupling reactions.…”
Section: Methodsmentioning
confidence: 99%